Pendampingan Pembuatan Website untuk Pengembangan Desa Digital di Desa Baros, Kabupaten Serang - Dewanto Samodro; Siti Maryam; Jati Satrio; Chairun Nisa Zempi (IKRA-ITH ABDIMAS, 2023)
The use of a website is a common thing by an institution. Almost every institution and organization inIndonesia used the website to reaches audiences and provides services. In addition to media information, thewebsite is also used for branding to marketing goods and services. Therefore, village as the lowest level ofgovernment in Indonesia also needs a website to provide services to villagers, disseminate information aboutthe village, and marketing main village products. This is a community service article in Baros Village, SerangRegency, which previously did not have a village website. The community service team facilitated a focusedgroupdiscussion (FGD) by presenting village stakeholders to formulate steps to create a website..